PENGARUH PSIKOLOGI MARKETING DAN DESTINASI WISATA TERHADAP KEPUASAN WISATAWAN DI OBJEK WISATA FARMHOUSE LEMBANG - Devi, Ghini Kuntala; MARINI, SRI; Pramono, Fajar (Universitas Bunda Mulia, 2025)
This study aims to determine marketing psychology, tourist destinations and tourist satisfaction and to determine how much influence the choice of marketing psychology and tourist destinations has on tourist satisfaction at the Farmhouse Lembang tourist attraction. This research method uses quantitative methods. The population in the study were tourists visiting the Lembang farmhouse tourist attraction. The number of samples in the study was taken using simple random sampling technique. The research analysis method uses path analysis to analyze the research results. The results showed that marketing psychology, tourist destinations and tourist satisfaction at Farmhouse Lembang tourist attraction are included in the good enough category. There is an influence of both marketing psychology and tourist destinations where the effect of tourist destinations is greater on tourist satisfaction. The influence of marketing psychology and tourist destinations has enough effect on tourist satisfaction and the rest is the influence of other variables not examined in this study that affect tourist satisfaction.